Wolman's disease: a case report with lipid, chromosome and electron-microscopic studies - Özsoylu, Şinasi; Gürgey, Aytemiz; Koçak, Nurten; Özoran, Yavuz; Özoran Görgen, Afet; Kerse, İlhan; Ciliv, Gönenç (The Turkish Journal of Pediatrics, 1977)
A case of Wolman's disease is reported in a Turkish infant, in whom the diagnosis was verified by the chemical composition of the lipid in the liver and the spleen. The parents were first cousins and the patient died due to hemorrhages and liver failure. Hepatosplenomegaly was documented on the 6th day of life and a protuberant abdomen was noticed at birth. Typical adrenal calcifications were shown at 45 days of age. Chromosomal studies did not disclose any abnormality and electron-microscopic examination of the liver and the spleen showed typical lysosomal lipid storage and cholesterol crystals.